2011
DOI: 10.1055/s-0030-1256767
|View full text |Cite
|
Sign up to set email alerts
|

New classification for probe-based confocal laser endomicroscopy in the colon

Abstract: A new classification for pCLE in the colon had a 'moderate' interobserver agreement for differentiating neoplasia from non-neoplastic tissue in the colon. The overall accuracy (81 %) for predicting neoplasia was acceptable and became excellent (94 %) when all five observers agreed. Future research should focus on refinement and validation of the classification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…In the second one, instead, we showed the switch from the inflamed to neoplastic mucosa in a patient with chronic ulcerative colitis (CUC) [5]. We confirmed previously reported data, according to Kuiper's work [44], in which they also proposed a new pCLE colon classification, highlighting the high level of accuracy of pCLE in identifying colonic intraepithelial neoplasia. Furthermore, we demonstrated the clinical applicability and predictive power of pCLE also in a group of aberrant colonic crypt foci (ACF) collected during laser confocal endomicroscopy, through the concordance between endoscopic and histological features (rate of architectural alterations in the absence or presence of epithelial dysplasia).…”
Section: Discussionsupporting
confidence: 83%
“…In the second one, instead, we showed the switch from the inflamed to neoplastic mucosa in a patient with chronic ulcerative colitis (CUC) [5]. We confirmed previously reported data, according to Kuiper's work [44], in which they also proposed a new pCLE colon classification, highlighting the high level of accuracy of pCLE in identifying colonic intraepithelial neoplasia. Furthermore, we demonstrated the clinical applicability and predictive power of pCLE also in a group of aberrant colonic crypt foci (ACF) collected during laser confocal endomicroscopy, through the concordance between endoscopic and histological features (rate of architectural alterations in the absence or presence of epithelial dysplasia).…”
Section: Discussionsupporting
confidence: 83%
“…Both techniques allow for the identification of cellular structures in vivo and the possibility of optical biopsies but will require intensive work and computer support before clinical application. While CLM is preferentially applied in flexible endoscopy to differentiate between benign and malignant alterations [59,60], OCT is currently a highly contributing imaging modality in ophthalmology [60]. However, in surgery, the need for an in-vivo applicable near microscopic imaging modality also exists, and we already demonstrated that the differentiation between benign and malignant tissue is possible in that way ( fig.…”
Section: Optical Methodsmentioning
confidence: 96%
“…Such visualization of nuclei was also described with cresyl violet in a proof-of-principle study that combined chromoendoscopy and fluorescence imaging with a single dye [15]. A classification system for pCLE has just been published and will undergo further evaluation [47]. A further study compared pCLE for prediction of histology of colonic lesions with virtual chromoendoscopy techniques (NBI, FICE) and found a higher sensitivity for pCLE with similar specificity in classification of colorectal polyps [48].…”
Section: Endomicroscopy For Colonic Neoplasiamentioning
confidence: 99%